Monitoring the coefficient of variation using a variable parameters chart - Yeong, Wai Chung; Lim, Sok Li; Khoo, Michael Boon Chong; Castagliola, Philippe (Taylor & Francis, 2018)
This article is the first of its kind which proposes a Variable Parameters (VP) chart to monitor the coefficient of variation (CV). Formulae for various performance measures and the algorithms to optimize these performance measures are proposed. The VP CV chart consistently outperforms the five alternative CV charts in the literature, for all shift sizes. Compared to the Exponentially Weighted Moving Average (EWMA) CV2 chart, the VP CV chart outperforms it for moderate and large shift sizes, while for small shift sizes, the EWMA CV2 chart outperforms the VP CV chart. Subsequently, the VP CV chart is implemented on an industrial example.